Tissue-Specific Hormonal Variations in Grapes of Irrigated and Non-irrigated Grapevines (Vitis vinifera cv. “Merlot”) Growing Under Mediterranean Field Conditions - Ribalta-Pizarro, Camila; Muñoz, Paula; Munné-Bosch, Sergi (Frontiers in Plant Science, 2021)
Agricultural practices in grapevines management include water restrictions due to its positive effect on wine quality, especially when applied at fruit ripening. Although the effects of water stress in some groups of phytohormones have already been described in leaves and whole grapes, information regarding tissue-specific variations in hormones during ripening in grapes is scarce. Field-grown grapevines from the cv. ‘Merlot’ were subjected to two differential water supplies, including only rainfed, non-irrigated vines (T0) and vines additionally irrigated (T1). Tissue-specific variations in the hormonal profiling of grapes were periodically evaluated from veraison to harvest. The hormonal profiling in leaves was also measured at the beginning and end of the season for comparison. Results showed that grape growth dynamics were transiently affected by the differences in water regimes, the increased water supply leading to an accelerated growth, slightly reduced accumulation of sugars and transiently lowered pH, although grape quality did not differ between treatments at harvest. Hormonal profiling of whole berries did not reveal any difference in the endogenous contents of phytohormones between treatments, except for a transient decrease in GA4 contents in T1 compared to T0 vines, which was not confirmed at the tissular level. Hormonal profiling at the tissue level highlighted a differential accumulation of phytohormones during ripening in berry tissues, with pulps being particularly poor in abscisic acid, jasmonic acid and salicylic acid contents, seeds particularly accumulating 1-amino-cyclopropane-1-carboxylic acid, gibberellins and zeatin-type cytokinins, and the skin being particularly rich in auxin and active cytokinins. Changes in water supply led to very small and transient changes in the endogenous contents of phytohormones in the seeds, pulp and skin of berries, the most remarkable variations being observed in cytokinin contents, which increased earlier (between 5 and 12 days after veraison [DAV]) but later kept more constant in the skin from T1 compared to T0 vines and were also three-fold higher at 40 DAV in seeds of T1 compared to T0 vines. It is concluded that small changes in water supply can trigger hormonal-driven physiological adjustments at the tissular level affecting the evolution of fruit growth and quality throughout grape berry ripening.